HAK KONSTITUSIONAL PARTAI POLITIK DALAM PENGUSULAN CALON PRESIDEN DAN WAKIL PRESIDEN PADA PEMILIHAN UMUM TAHUN 2019 - Asdhie Kodiyat MS, Benito (Fakultas Hukum Universitas Borneo Tarakan, 2017)
After the decision of Constitutional Court Number: 14/PUU-XI/2013 the judicial riview of the law number 42 of 2008 on presidential and vice presidential elections has no binding legal force and the implementation of legislative and presidential election and vice president are held simultaneously, which then led to a long debate in the Legislative Assembly. The debate concerns the threshold of nomination of President and Vice President in 2019. In the meetings of the people?s representative council, the proposed 20 percent presidential and vice presidential nomination threshold has been ratified aince the enactment of the new electoral law, namely law number 7 of 2017 about general election. The problem is, how to calculate the threshold of presidential and vice presidential nominations for new political parties of 2019 election participants who do not yet have a valid national vote, whereas the political parties participating in 2019 general election have the same constitutional rights in proposing the presidential and vice presidential nominees, the constitutional right of the new political party is inevitavly unenforceable and the right to nominate a presidential and vice presidential candidate must be ignored, whereas granting constitutional rights to new political parties of election participants will strengthen the presidential system adopted in Indonesia and will offer many political options for the Indonesian people who reflecting a healthy election process.